Islam and the West: Tariq Ramadan and the Discourse of Religion of Peace for a Global Understanding - Abdul Razak Abdulroya Panaemalae; Zaenuddin Hudi Prasojo (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
As the world is increasingly globalized, culture and human thought are developing in a different way because it is shaped by culture and climate of the local environment. In the West, in particular, Muslims confront the issues currently generated by the culture and philosophy of Western civilization which is very different in terms of the frame of thought. Therefore, to be adapted to the Western/European environment and so Islam will be able to grow, the modification of the format without changing the original teachings of Islam are highly required. Even this method is very suitable based on dynamic Islam. Tariq Ramadan, indeed, is seen as a prominent Muslim thinker who attempt to explore the historical tradition of Islam, or the Prophet’s biography, to be applied to the western/European tradition whose typical civilization might prevent Islam from flourishing if global Islamic values are not applied to the current world. In other words, if the same methods are used as practiced in the Islamic tradition in the East, the possibility is that Islam will not thrive in the West. In his book, In the Footsteps of the Prophet: Lessons from the Life of Muhammad, he clearly shows how the biography of the Prophet is extracted of the essence of teaching to be used as a catalyst in a new life or to be adjusted to the context of the current globalized world.